2007
DOI: 10.1111/j.1467-7687.2007.00600.x
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic gradients predict individual differences in neurocognitive abilities

Abstract: Socioeconomic status (SES) is associated with childhood cognitive achievement. In previous research we found that this association shows neural specificity; specifically we found that groups of low and middle SES children differed disproportionately in perisylvian/language and prefrontal/executive abilities relative to other neurocognitive abilities. Here we address several new questions: To what extent does this disparity between groups reflect a gradient of SES-related individual differences in neurocognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

89
720
4
41

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 879 publications
(854 citation statements)
references
References 59 publications
89
720
4
41
Order By: Relevance
“…Several significant direct effects emerged that were in line with the premises of the mediation model and corroborated our hypotheses. Regarding the environmental factors, our data showed that SES and HLE are directly associated with language, replicating previous findings (Farah et al, 2006;Hackman & Farah, 2009;Hart & Risley, 1992;Hoff & Tian, 2005;McKean et al, 2015;Noble et al, 2007;Roberts et al, 2005;SĂ©nĂ©chal & LeFevre, 2014;Wood, 2002). Moreover, consistently with the literature across kindergartners, first graders, and preadolescents (Evans & Schamberg, 2009;Farah et al, 2006;Hackman et al, 2014;Sarsour et al, 2011;Waber et al, 2007), disadvantaged SES was related to impaired temporary memory.…”
Section: The Role Of Ses and Hlesupporting
confidence: 91%
See 1 more Smart Citation
“…Several significant direct effects emerged that were in line with the premises of the mediation model and corroborated our hypotheses. Regarding the environmental factors, our data showed that SES and HLE are directly associated with language, replicating previous findings (Farah et al, 2006;Hackman & Farah, 2009;Hart & Risley, 1992;Hoff & Tian, 2005;McKean et al, 2015;Noble et al, 2007;Roberts et al, 2005;SĂ©nĂ©chal & LeFevre, 2014;Wood, 2002). Moreover, consistently with the literature across kindergartners, first graders, and preadolescents (Evans & Schamberg, 2009;Farah et al, 2006;Hackman et al, 2014;Sarsour et al, 2011;Waber et al, 2007), disadvantaged SES was related to impaired temporary memory.…”
Section: The Role Of Ses and Hlesupporting
confidence: 91%
“…Verbal temporary memory was found impaired in preterm individuals in a longitudinal cohort of 919 adults from the Helsinki Birth Cohort Study, supporting memory as a target of direct effects of prematurity and suggesting that such effects may have long-lasting consequences (Heinonen et al, 2015). Robust associations have also been found between both SES and HLE, and temporary memory (Evans & Schamberg, 2009;Farah et al, 2006;Hackman et al, 2014;Noble et al, 2007;Peterson, et al, 2013;Sarsour et al, 2011). For example, SES in children attending primary school accounted for 5.5% of the variance in vWM (Noble et al, 2007).…”
Section: Memory As a Mediator Between Environmental And Biological Famentioning
confidence: 95%
“…While the evidence is mixed as to whether SES relates to WM ability as such (Aran-Flippetti, 2013;Hackman, Betancourt, Gallop, Romer, Brodsky, Hurt, & Farah, 2014;Noble, Norman, & Farah, 2005;Noble, McCandliss, & Farah, 2007;but see, Engle, Santos, & Gathercole, 2008;Alloway, Alloway, & Wootan, 2014), it is relevant to the development of general cognitive abilities (Farah, Shera, Savage, Betancourt, Brodsky, & Hurt, 2006;Hackman & Farah, 2009). When comparing across other studies, it is important to be mindful of the possible role of extraneous factors such as SES on task performance.…”
Section: Discussionmentioning
confidence: 99%
“…6 Two of the domains of mental development in which we have shown highly significant results -short term, or working, memory (a measure of executive function) and language -have been identified through neurologic studies to be the most sensitive to differences in SES. 51,52 Future research should further explore the relationship between SES change in and child development in this context.…”
Section: Cognitive Motor and Language Developmentmentioning
confidence: 99%